A prospective study of de novo scoliosis in a community based cohort - Kobayashi, Tetsuya; Atsuta, Yuji; Takemitsu, Masakazu; Matsuno, Takeo; Takeda, Naoki (Spine (Philadelphia, Pa. 1976), 2006)
A 12-year prospective study of de novo scoliosis in a community based cohort. OBJECTIVE.: To investigate factors associated with development of de novo scoliosis. De novo scoliosis is becoming one of the most prevalent findings in the aging spine, and this condition is associated not only with severe back or leg symptoms but also with complicated surgical outcomes. Cross-sectional studies were limited in distinguishing de novo scoliosis from preexisting deformities, and there had been controversies over the etiology of degenerative scoliosis. Community based volunteers were recruited, then examined by orthopedic physicians. Radiologic measurements using entire spine radiographs included the angle of scoliosis and sagittal spinal curvatures, sagittal spinal balance, grade of bone atrophy, number of degenerated discs, and vertebral fractures. We defined radiologic parameters, the disc index, and lateral osteophyte difference to evaluate the asymmetrical spinal degeneration. A total of 60 subjects aged 50-84 years and without scoliosis at baseline were selected and followed for a mean of 12.0 years. De novo scoliosis >or=10 degrees developed in 22 subjects, and logistic regression analysis revealed that the baseline disc index and lateral osteophyte difference values were independent predictors (P < 0.05). Incidence of de novo scoliosis was predictable by assessing asymmetric disc degeneration in frontal radiograph. More than 20% decrease in unilateral disc height or more than 5 mm longer osteophyte on one side led to increased incidence of de novo scoliosis, which might also influence long-term results of spinal surgery.